Primary Myiasis in Surgical Wound of Mandible Symphisis Fracture - Gustavo A. Lauand; Felipe G. G. P. Lima; Ricardo P. da Silva; Larissa Rodrigues Santiago; Jonas B. Dantas; Cláudia J. Silva; Lair M. Furtado (Hindawi Limited, 2019)
A 42 year old patient was referred to the Department of Oral and Maxillofacial Surgery of the Federal University of Uberlândia, for treatment of mandibular fractures (condyles and symphysis), a victim of a run over. The symphysis was surgically approached, using as surgical access the pre-existing laceration in the submental region. Five days after discharge, the patient returned with dehiscence of the wound and physical examination showed infestation by larvae in the symphysis. Mechanical removal and debridement were performed under local anesthesia, where plate exposure was noted. The patient underwent oral ivermectin therapy, intravenous antibiotic therapy and a thorough debridement was performed under general anesthesia due to the invasion of deep spaces in the supra-hyoid region. After 2 weeks, it presented with purulent drainage at the site. The miniplates were replaced by a 2.4 mm reconstruction plate and antibiotic therapy was maintained. Due to the social risk, the patient remained hospitalized for 45 days, when he was discharged with outpatient return, but did not attend the returns.